2012
DOI: 10.2351/1.4719936
|View full text |Cite
|
Sign up to set email alerts
|

In-process measuring procedure for sub-100 nm structures

Abstract: Fast and nondestructive laser light scattering measurements characterize the quality of surfaces with sub-100 nm structures during the production process. The aim is to detect defective surface structures. The measurement procedure is based on a primary comparison of measured speckle patterns with a multitude of numerically calculated speckle patterns caused by defect-free and defective surface structures. The comparison shows characteristic light scattering effects, which have to be detected by the in-process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…An analytical study on light scattering from micrometer range surfaces showed that the out-ofplane scattering signatures of particulate contamination, subsurface defect, and surface microroughness differ significantly [18]. Another study on the scatterometric defect evaluation of ZnO nanograss surface compared numerical simulation results with experimental results from two different setups [10]. This demonstrated that a numerical simulation of modelled nanostructures having randomized spatial distributions, which are approximated from real samples, yields qualitatively similar light scattering results to that of the experiments.…”
Section: State Of the Artmentioning
confidence: 88%
See 3 more Smart Citations
“…An analytical study on light scattering from micrometer range surfaces showed that the out-ofplane scattering signatures of particulate contamination, subsurface defect, and surface microroughness differ significantly [18]. Another study on the scatterometric defect evaluation of ZnO nanograss surface compared numerical simulation results with experimental results from two different setups [10]. This demonstrated that a numerical simulation of modelled nanostructures having randomized spatial distributions, which are approximated from real samples, yields qualitatively similar light scattering results to that of the experiments.…”
Section: State Of the Artmentioning
confidence: 88%
“…the evaluation of scattered light, that works fast, non-invasive and is applicable also inprocess, has the potential to meet the time resolution and robustness requirements of a mass production line. It analyses the intensity distribution of laser light scattered from surfaces, in order to retrieve topography information, including structural defects [10,11].…”
Section: State Of the Artmentioning
confidence: 99%
See 2 more Smart Citations
“…A plethora of thermomechanical effects were indicated with the emergence of pressure waves [132] in the aftermath of plasma relaxation close to microexplosion conditions [133]. Alternative methods are based on scattering and diffraction techniques with capabilities to observe nanoscale structures, as first applied on surfaces [134,135]. Direct diffraction techniques were used either to steer open optimization loops on bulk nanogratings [136] or to detect the dynamic onset of a diffractive response of laserinduced regular structures [137].…”
Section: Observation and Control: Dynamic Coupling Between Light And mentioning
confidence: 99%